1993
DOI: 10.1093/eurheartj/14.10.1297
|View full text |Cite
|
Sign up to set email alerts
|

Surgical revascularization in the treatment of ventricular tachycardia and fibrillation exposed by exercise-induced ischaemia

Abstract: The role of myocardial revascularization in the treatment of malignant ventricular arrhythmias is not well defined. Our hypothesis was that in patients with ventricular tachycardia or fibrillation exposed by exercise-induced ischaemia, the acute transient ischaemia plays a principal causal role, and that in these patients surgical myocardial revascularization alone might be an effective treatment. Among 1100 consecutive patients undergoing isolated coronary artery bypass surgery (CABG) 30 patients (2.7%) chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…260 Among these patients, CABG can suppress malignant arrhythmias and reduce subsequent episodes of cardiac arrest, 261,262 especially if the arrhythmias are related to ischemia. 263 On the other hand, CABG may not mitigate all the conditions predisposing to ventricular arrhythmias, as in the case of patients with sustained monomorphic ventricular tachycardia and prior MI, and concomitant ICD insertion after CABG may be warranted in such patients.…”
Section: Devicesmentioning
confidence: 99%
“…260 Among these patients, CABG can suppress malignant arrhythmias and reduce subsequent episodes of cardiac arrest, 261,262 especially if the arrhythmias are related to ischemia. 263 On the other hand, CABG may not mitigate all the conditions predisposing to ventricular arrhythmias, as in the case of patients with sustained monomorphic ventricular tachycardia and prior MI, and concomitant ICD insertion after CABG may be warranted in such patients.…”
Section: Devicesmentioning
confidence: 99%
“…In survivors of cardiac arrest who have severe but operable CAD, CABG can suppress the appearance of arrhythmias, reduce subsequent episodes of cardiac arrest, and result in a good long-term outcome (271)(272)(273). It is particularly effective when an ischemic cause of the arrhythmia can be documented (for instance, when it occurs with exercise) (275). Still, because CABG may not alleviate all the factors that predispose to ventricular arrhythmias, concomitant insertion of an implantable cardioverter-defibrillator is often warranted (276).…”
Section: Class Imentioning
confidence: 99%
“…CR can potentially alter all these mechanisms 1 and reduce the risk for ventricular arrhythmias during the first years after the procedure. Several studies have suggested that CR is associated with ventricular arrhythmia risk‐reduction 14,15 . Most recently, we have shown in post‐MI patients with left ventricular dysfunction enrolled in MADIT‐CRT that the risk of life threatening ventricular arrhythmias, the probability of antitachycardia pacing, and appropriate ICD shocks increase as a function of time elapsed since the revascularization procedure 3 .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have suggested that CR is associated with ventricular arrhythmia risk-reduction. 14,15 Most recently, we have shown in post-MI patients with left ventricular dysfunction enrolled in MADIT-CRT that the risk of life threatening ventricular arrhythmias, the probability of antitachycardia pacing, and appropriate ICD shocks increase as a function of time elapsed since the revascularization procedure. 3 Although the response by physicians for appropriate ICD therapy is commonly a sense of relief that a ventricular arrhythmia was treated and possibly sudden death was averted, there are several studies 4,5 that showed that in highrisk cardiac patients, the reduction in arrhythmic mortality with an ICD may translate into a subsequent increase in the risk for heart failure and nonsudden cardiac mortality.…”
Section: Possible Mechanism For the Time-dependent Effect Of Cr On Lomentioning
confidence: 99%